Reevaluation of the type species and redescription of five species of Edessa (Heteroptera: Pentatomidae: Edessinae) - Silva, Valeria Juliete Da; Rider, David A.; Fernandes, Jose Antonio Marin (Zootaxa, 2017)
In accordance with the rules in the International Code of Zoological Nomenclature, the type species for the genus Edessa Fabricius, 1803 is now recognized to be Cimex antilope Fabricius, 1798 rather than the previously recognized Cimex cervus Fabricius, 1787. Edessa antilope is redescribed, as well as the following four species that have in the past been related or compared to E. antilope: E. arabs (Linnaeus, 1758) from French Guiana, Costa Rica and Panama (new record), E. helix Erichson, 1848 from Costa Rica, Panama, Venezuela, Suriname (new record), Guyana, Brazil (new record), Bolivia (new record) and Argentina (new record), E. ibex Breddin, 1903 from Costa Rica, Panama (new record), Ecuador, Brazil (new record), Peru and Bolivia (new record), and E. taurina Stål, 1862 from Mexico, Guatemala, Belize (new record), Honduras (new record). The distribution of Edessa antilope is expanded to Venezuela. The female of E. antilope and the male of E. taurina are described for the first time. Edessa antilope is removed from the synonymy of E. arabs and reinstated as valid species; additionally, E. costalis Stål, 1872 is removed from the synonym of E. helix and is placed as a junior synonym of E. antilope. Edessa saiga Breddin, 1903 is considered a junior synonym of E. ibex. Lectotypes are designated for all species. A key is provided for the identification of the species.